Time Series Analysis of Baghdad Rainfall Using ARIMA Method - Ali, Sawsan (Iraqi Journal of Science, 2024)
Monthly rainfall data of Baghdad meteorological station were taken to study the time behavior of these data series. Significant fluctuation,very slight increasing trend and significant seasonality were noticed. Several ARIMA models were tested and the best one were checked for the adequacy. It is found that the SEASONAL ARIMA model of the orders SARIMA(2,1,3)x(0,1,1) is the best model where the residual of this model exhibits white noise property, uncorrelateness and they are normally distributed. According to this model, rainfall forecast for four years was also achieved and showing similar trend and extent of the original data.